Contribution to the study of human bartonellosis - Alzamora Castro, Víctor (1942)
Bartonella baciliformis is a micro-organism, which, by reason of its biological characteristics, occupies an intermediate position between Typical Rieketsia and common Bacteria. 2. Severe Anemia, or Carríon's Fever formerIy called "Oroya Fever", is the acute form of Bartonellosis. In the latter, the Bartonella forms an important colonization of the cellular system favorably to itself: furthermore, it spreads abundantly in the circulating blood. 3. During the course of acute Bartonelosis, the number of germs in the circulating blood, diminish progressively, and a similar process is set up almost simultaneously in the depth of the organs. The cells capable of armouring the virus, acquire a relative immunity, which, however, is sufficient to allow the improvement preceding the appearance of the verrugas to take place. 4. The giving off of endo-toxins, due to the destruction of the germs, probably constitutes the mechanism of the clinical symptoms. 5. Acute Bartonelosis is very often associated with Salmonelosis, wich has a dreadful meaning for the patient. 6. There is, between acute Bartonelosis, and the Bartonelosis devoid of clinical manifestations, a scale of intermediate forms, representing all the possible manners of existence of the xeno-parasitic complex, and which are made apparent by various clinical patterns. 7.Human Bartonelosis, invariably means a struggle between the cellular system and the causal agent. 8.In human Bartonelosis, inmunity is essentially a cellular phenomenon.